Varietas Kelapa Sri Gemilang untuk Lahan Pasang Surut [Sri Gemilang Coconut Variety for Tidal Area] - Donata Suriaty Pandin; E. T. Tenda; Meity T. Tulalo; Ismail Maskromo (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
Indonesia has a tidal swampy area of about 33.4 million hectares, from which + 20 million hectares could be cultivated as a coconut plantation. If it is used optimally, the area could play an important role in supporting the national food security. Several technologies have been produced and applied, and the use of adaptive varieties in tidal land, can improve and enhance the productivity of the land. The availability of superior tall coconut varieties to meet the required coconut seeds for coconut development program is still limited. All of the coconut high yielding varieties launched by the Minister of Agriculture are suitable for dry land only, and not for tidal one. Sri Gemilang, a coconut variety grown in tidal land in Parit Sialang Krubuk, Hidayah Village, Pelangiran District, Indragiri Hilir, Riau Province was evaluated from 2012 to 2016. Observations showed that the production of frutis and copra were relatively stable, averaging above 3.0 tons of copra/ha/year. Sri Gemilang variety with a potential endosperm weight of about 518 g/nut was selected as palms for superior seed sources. Weight of nuts decreased to about 433 g/nut during observation in 2016, after long dry season. However, it was still higher than the control varieties, DTA (371 g/nut) and DMT (366 g/nut) grown on the same tidal land. If the weight of coconut meat is converted to the production of copra/ha, it can reach > 3.0 tons of copra/ha/year, while DTA and DMT grown on tidal land was only 1.6 tons and 1.56 tons of copra/ha/year, respectively. The low weight of endosperm of DTA and DMT is presumably because both varieties which typically grow well on dry land, less adaptable on tidal land. ABSTRAKIndonesia memiliki lahan rawa pasang surut 33,4 juta hektar, sekitar 20 juta hektar dapat diusahakan sebagai perkebunan kelapa. Jika dimanfaatkan secara optimal akan berperan penting dalam mendukung swasembada dan ketahanan pangan nasional. Beberapa teknologi telah dihasilkan dan diterapkan, penggunaan varietas adaptif di lahan pasang surut, dapat memperbaiki dan meningkatkan produktivitas lahan. Jenis kelapa Dalam unggul yang tersedia masih sangat terbatas sehingga belum dapat memenuhi kebutuhan benih untuk program pengembangan kelapa. Varietas unggul kelapa yang telah dilepas oleh Menteri Pertanian, semuanya memiliki habitat pada lahan kering, sedangkan habitat pada lahan pasang surut belum ada. Kelapa Dalam Sri Gemilang tumbuh di lahan pasang surut, yaitu di Parit Sialang Krubuk, Desa Hidayah, Kecamatan Pelangiran, Kabupaten Indragiri Hilir, Provinsi Riau. Hasil penelitian tahun 2012 hingga 2016, menunjukkan bahwa produksi buah kelapa dan kopra relatif stabil, yaitu rata-rata di atas 3,0 ton kopra/ha/tahun. Pada varietas kelapa Sri Gemilang dilakukan pemilihan Pohon Induk dengan potensi rata-rata berat daging buah 518 g/butir. Kemarau panjang pada tahun 2015 mengakibatkan berat daging buah turun pada tahun 2016, yaitu 433 g/butir, namun lebih tinggi dibandingkan kelapa DTA (371 g/butir) dan DMT (366 g/butir) sebagai varietas pembanding yang ditanam di lahan pasang surut. Jika berat daging buah kelapa dikonversi ke produksi kopra per hektar maka kelapa Dalam Sri Gemilang mencapai > 3,0 ton kopra/hektar/tahun, sedangkan kelapa DTA dan DMT yang ditanam di lahan pasang surut masing-masing 1,6 ton dan 1,56 ton kopra/hektar/tahun. Hal ini menunjukkan bahwa Kelapa DTA dan DMT yang biasanya tumbuh baik dan berproduksi tinggi pada lahan kering, kurang adaptif pada lahan pasang surut.